The GlideScope with modified Magill forceps facilitates nasogastric tube insertion in anesthetized patients: A randomized clinical study - Kim, Han Joon (J Int Med Res, 2018)
OBJECTIVE: Insertion of a nasogastric tube (NGT) in patients who have been intubated with an endotracheal tube while under general anesthesia can cause difficulties and lead to complications, including hemorrhage. A visualization-aided modality was recently used to facilitate NGT insertion. Some studies have focused on the role of modified Magill forceps, which have angles similar to those of the GlideScope blade (Verathon, Bothell, WA, USA). METHODS: Seventy patients were divided into a control group (Group C) and an experimental group (GlideScope and modified Magill forceps, Group M). RESULTS: The total NGT insertion time was significantly shorter in Group M than C (71.3 ± 22.6 vs. 96.7 ± 57.5 s; mean difference, –25.3 s; 95% confidence interval [CI], 20.8–71.5). There were also significantly fewer mean insertion attempts in Group M than C (1.0 ± 0.0 vs. 2.11 ± 0.93). The success rate for the first attempt in Group C was 37.1%, while that in Group M was 100% (relative risk, 2.7; 95% CI, 1.7–4.1). CONCLUSION: The use of the GlideScope with modified Magill forceps for insertion of an NGT in patients who are already intubated and under general anesthesia will shorten the insertion time and improve the success rate.